2017
DOI: 10.3390/nu9121372
|View full text |Cite
|
Sign up to set email alerts
|

Oligofructose Provides Laxation for Irregularity Associated with Low Fiber Intake

Abstract: Inadequate dietary fiber intake contributes to the prevalent irregularity and constipation in Western countries. Although eating adequate amounts of fibers from fiber-rich foods, foods with added fibers and dietary fiber supplements is considered the first option for improving laxation, the efficacy can vary among types of fibers. The present study is a randomized control trial that included healthy adult participants with ≤3 bowel movements/week and a habitual low dietary fiber intake in a parallel design to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 34 publications
0
16
0
3
Order By: Relevance
“…The humectant water binding capacity of prebiotic carbohydrates also has the effect of softening stools, making passage easier. 111,112 There are surprisingly few studies on the effect of prebiotics on bowel function, although they have consistently led to improvements in stool consistency and defecation frequency in randomized trials 113,114 [H3] Metabolic effects. As discussed earlier, prebiotic intervention results in the elaboration of SCFAs that can act to improve barrier function in the gut and prebiotic intervention with GOS has shown improvements in barrier function in vivo.…”
Section: [H1] Prebioticsmentioning
confidence: 99%
“…The humectant water binding capacity of prebiotic carbohydrates also has the effect of softening stools, making passage easier. 111,112 There are surprisingly few studies on the effect of prebiotics on bowel function, although they have consistently led to improvements in stool consistency and defecation frequency in randomized trials 113,114 [H3] Metabolic effects. As discussed earlier, prebiotic intervention results in the elaboration of SCFAs that can act to improve barrier function in the gut and prebiotic intervention with GOS has shown improvements in barrier function in vivo.…”
Section: [H1] Prebioticsmentioning
confidence: 99%
“…However, there was no separation at the end of the growing phase, an indication that that fibre type did not affect beta diversity at the end of the growing phase influenced by the type consumed, being primarily mediated by effects on the microbiome and fermentation products (Canfora et al, 2017;Cheng et al, 2017;Venkataraman et al, 2016), and effects of these on the host. Inulin and cellulose are two major fibre types that are used in human diets for their digestive and metabolic health benefits (Ahmed & Rashid, 2017;Buddington, Kapadia, Neumer, & Theis, 2017;Morowitz et al, 2017). These effects are primarily associated with continuous presence of these fibres in regular diets.…”
Section: Discussionmentioning
confidence: 99%
“…Four adult studies found beneficial effects on improvement in bowel symptoms with prebiotic fibers [74][75][76][77] . Marteau et al demonstrated that 15 g of inulin supplementation improved constipation and quality of life in elderly people 74 .…”
Section: Prebiotic Fibers (Oligosaccharides Inulin)mentioning
confidence: 99%
“…Another study in the elderly population showed improvement in constipation in 9 out of 10 subjects on inulin consumption 75 . Orafti  , a granulated inulin powder, was studied in two of the trials 76,77 . Micka et al found Orafti  significantly increased stool frequency compared to placebo (p=0.038) 76 .…”
Section: Prebiotic Fibers (Oligosaccharides Inulin)mentioning
confidence: 99%